Nurses’ Caring Behavior, Parental Anxiety and Satisfaction in Pediatric Inpatient War - Rifai, Susan Irawan; Mukaromah, Raihany S.; Nugraha, Dedep; Fuadah, Novitasari T. (GLOBAL HEALTH SCIENCE GROUP, 2024)
Caring behavior should consistently be applied by nurses in all care settings, including pediatric inpatient wards.Children undergoing hospitalization will experience traumatic and highly stressful events, this condition can lead to anxiety in parents. Caring can reduce anxiety for both the child and parents. Furthermore, if nurses implement caring optimally, patients will feel satisfied, leading to an improvement in the quality of nursing services. This research aims to identify the relationship between nurses' caring behavior and parental satisfaction and anxiety in pediatric inpatient wards. The research design utilizes descriptive correlational with a cross-sectional approach involving 97 parents sampled through quota sampling. The instrument for measuring caring behavior uses the Caring Assessment Tools (CAT), a satisfaction questionnaire containing five SERVQUAL dimensions, and a parental anxiety questionnaire using the Zung Self-Rating Anxiety Scale. Sprearman rank was used as data analysis. The research results indicate that almost all respondents (90.7%) do not feel anxious, the majority of respondents (75.3%) are highly satisfied with the service, and most of respondentds (62.9%) assess nurses' caring behavior as adequate. Spearman-ranks test results show a significant relationship between anxiety and satisfaction with nurses' caring behavior (p=0.036 & p=0.001). These findings suggest that the better the nurses' caring behavior, the lower the level of parental anxiety, and the higher the patient satisfaction in the pediatric inpatient ward. Nurses need to undergo training and develop caring attitudes and behaviors in delivering nursing services.